EROSI IMAGO DEI DAN MANDAT BUDAYA:: BENCANA HIDROMETEOROLOGI INDONESIA SEBAGAI KONSEKUENSI KEGAGALAN ETIKA KITAB KEJADIAN - Kuswientoro, Oktafian (Jurnal Teologi RAI, 2026)
This research is motivated by the fact that more than 98% of natural disasters that occur in Indonesia are dominated by hydrometeorology (floods, landslides, and forest and land fires) caused by human factors. This natural environmental crisis is seen as a manifestation of theological erosion or the failure of humanity to live the Image of God (Imago Dei) responsibly. Using the Contextual Hermeneutics method, this study interprets the meaning of Kābaš (conquer) and Rādâ (power) from Genesis 1:28 with the meanings of Abad (to serve) and Shamar (guardian) from Genesis 2:15. This study aims to analyze the ethical relationship of cultural mandates with environmental crises and to offer an update of environmental theology with a focal point of Imago Dei restoration. The novelty of this study is that it directly links hydrometeorological disasters with the failure of biblical ethical praxis. Previous research has mainly tended to the ontological dimension of humans. The results of the study show that the hydrometeorological disaster in Indonesia is an ethical consequence of man’s theological fall into sin, namely greed and selfish anthropocentrism. The solution of this study emphasizes the need to renew the cultural mandate in order to balance Kābaš (conquer) with Abad (to serve) and Shamar (guardian). The church in the modern era today is expected to carry out its prophetic responsibilities through ecopedagogy and fight for ecological and social justice to protect vulnerable groups affected by disasters